2015
DOI: 10.1292/jvms.14-0490
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient starvation affects expression of LC3 family at the feto-maternal interface during murine placentation

Abstract: LC3 − the mammalian homolog of Atg8 − was found as autophagosome membrane binding protein in mammals and widely used as an autophagosomal marker. LC3A, B and C show different expression patterns in each tissue. The aim of this study was to reveal the differences of expression patterns among LC3 families in mouse placenta under normal condition and nutrient starving condition. LC3A and B were highly expressed in decidual cells. LC3A and B were increased in D14 compared with D12 and D16 in mouse placenta, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
11
1
Order By: Relevance
“…S5). This is consistent with the common view that LC3s and GABARAPs have concerted but also can exhibit distinct, non-overlapping intracellular localizations, which is accompanied with at least partial functional divergences 2,16,22,24,25 .
Figure 5Anti-GABARAP (8H5) antibody detects endogenous GABARAP within some but not all LC3B + structures. ( A ) HAP1 parental and GABARAP KO cells were incubated for 3 h with 100 nM BafA1 in growth factor depleted medium.
…”
Section: Resultssupporting
confidence: 85%
“…S5). This is consistent with the common view that LC3s and GABARAPs have concerted but also can exhibit distinct, non-overlapping intracellular localizations, which is accompanied with at least partial functional divergences 2,16,22,24,25 .
Figure 5Anti-GABARAP (8H5) antibody detects endogenous GABARAP within some but not all LC3B + structures. ( A ) HAP1 parental and GABARAP KO cells were incubated for 3 h with 100 nM BafA1 in growth factor depleted medium.
…”
Section: Resultssupporting
confidence: 85%
“…Impairment of autophagy by soluble endoglin weakens the invasion and vascular remodelling ability of EVTs, leading to poor placentation. In support of these findings, another study found that autophagy is highly induced in maternal decidual cells and the placenta (Hiyama et al ., ).…”
Section: The Roles Of Autophagy In the Mammalian Life Cyclementioning
confidence: 97%
“…The expression levels of LC3A and LC3B, but not LC3C, are higher in the decidua basalis than in the labyrinth layer. 30 LC3B expression primarily increases in the labyrinth and decidua basalis in response to starvation, which is a general inducer of autophagy in the murine placenta. Although the underlying mechanisms by which starvation increases LC3B expression are not known, LC3B could be responsible for autophagy response in the murine placenta.…”
Section: Role Of Autophagy In In Vivo Embryogenesis and Placentationmentioning
confidence: 99%
“…The LC3 family of proteins is divided into three types: LC3A, LC3B and LC3C. The expression levels of LC3A and LC3B, but not LC3C, are higher in the decidua basalis than in the labyrinth layer 30 . LC3B expression primarily increases in the labyrinth and decidua basalis in response to starvation, which is a general inducer of autophagy in the murine placenta.…”
Section: Role Of Autophagy In In Vivo Embryogenesis and Placentationmentioning
confidence: 99%